2023
DOI: 10.1002/jid.3755
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sustainable development status of micro and small enterprises in Debre Berhan town, central Ethiopia

Abstract: This study investigates the sustainable development status of micro and small enterprises (MSEs) in Debre Berhan town in five major manufacturing sub‐sectors (textile and garment, agro‐processing, woodwork, food processing and beverage and metal works and engineering). The sustainable development status of the selected MSEs was evaluated using 16 indicators for the three pillars of sustainable development (economic, social and environmental). The results showed that economic sustainability was at a ‘low’ level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Tere are several types of livestock feed and fodder resources in Ethiopia, the common of which are subject to seasonal availability, particularly in dry areas. Ethiopian livestock feed resources were classifed as pasture land, crop residues after grazing, improved pasture, pasture trees and browse, and agroindustrial by-products [46]. In pastoral and agropastoral livestock production systems, rangeland grazing and browsing (foliage and pods of trees and shrubs) are the primary sources of feed while cropping residues, stubble grazing, and conserved forages are used on occasion.…”
Section: Challenges and Constraints Of Livestock Feed Resourcementioning
confidence: 99%
“…Tere are several types of livestock feed and fodder resources in Ethiopia, the common of which are subject to seasonal availability, particularly in dry areas. Ethiopian livestock feed resources were classifed as pasture land, crop residues after grazing, improved pasture, pasture trees and browse, and agroindustrial by-products [46]. In pastoral and agropastoral livestock production systems, rangeland grazing and browsing (foliage and pods of trees and shrubs) are the primary sources of feed while cropping residues, stubble grazing, and conserved forages are used on occasion.…”
Section: Challenges and Constraints Of Livestock Feed Resourcementioning
confidence: 99%
“…Furthermore, it has been shown that rodent reproduction is affected by rainfall patterns (Odhiambo et al, 2005). According to Alemayehu and Bekele (2013) breeding in rodents reaches peaks towards the end of the rainy season when resources are plenty.…”
Section: Discussionmentioning
confidence: 99%